Web-Based Culture Information System of Literature Besemah City of Pagar Alam - Puspita, Desi; Mukti, Yogi Isro' (Sekolah Tinggi Teknologi Adisutjipto, 2019)
The purpose of this research is to create a Web-based Literature Culture Information System Besemah Pagar. Besemah Literary Culture comes from the besemah tribe that grew up in Kota Pagar Alam. Besemah literature is now rarely heard by the Pagar Alam people inside and outside the City of Pagar Alam and is also almost unknown to the public, especially Pagar Alam among young people today. The system development method used is Rapid Application Development. With the web-based information system program, the public will gain knowledge about the literary culture that is weak in the City of Pagar Alam, and also help disseminate information in the introduction of the culture and literature to the public at large to increase outside tourists in supporting the City of Pagar Alam program. Tests carried out using Black Box Testing with no error results. The results of research in the form of Web-based Literature Culture Information System Weak Besagar Pagar that can be implemented and used by the general public.